Pengaruh Efektivitas Pengendalian Intern Terhadap Tingkat Keberhasilan Kredit Pada Pt. Suzuki Finance Indonesia (SFI) Cabang Manado - Ferly Olan Rumengan; Frendy A.O. Pelleng; Olivia F. Walangitan (Universitas Sam Ratulangi, 2018)
Loan activity by a finance company is an activity that has high risk, there are many problems or constraints - constraints that result in loss. Factors - factors causing the occurrence of problem loans, including bad loans, installment payments, monitoring and pengelolah internal credit, and so on. Therefore, whether the effectiveness of internal control affects the success rate of credit. This study aims to determine how much influence the effectiveness of internal control of credit success rate at PT. Suzuki Finance Indonesia Branch Manado. Credit by Rivai (2013)